Power-to-gas: CO2 methanation in a catalytic fluidized bed reactor at demonstration scale, experimental results and simulation. Issue 50 (August 2021) - Hervy, Maxime; Maistrello, Jonathan; Brito, Larissa; Rizand, Mathilde; Basset, Etienne; Kara, Yilmaz; Maheut, Marion
Graphical abstract: Highlights: CO2 methanation tests were performed in a demonstration fluidized bed reactor. Maximum possible conversions were achieved regardless of the operating conditions. Different process chains were evaluated through process simulation. SNG meeting the H natural gas European standards can be produced by this reactor. This technology appears as an efficient and flexible solution for a PtM application. Abstract: CO2 methanation tests were carried out in a demonstration scale fluidized bed reactor (400 kWSNG capacity) to investigate its efficiency and flexibility towards operating conditions fluctuations associated with Power-to-Methane (PtM) production units. A wide range of operating conditions were explored: pressure (2–4 bara), reaction temperature (260−375 °C), H2 /CO2 inlet ratio (1.5–4.8), heat released by the reaction exothermicity (13.4–32.7 kWth ), and U/Umf (2.2–7.2). Whatever the operating conditions, this technology (reactor and catalyst) reached the maximum possible conversion, i.e. the thermodynamic equilibrium, in only one step. These excellent performances resulted from efficient management of methanation exothermicity (temperature gradient in the fluidized bed is lower than 20 °C) and optimized catalyst activity (even at low temperature: 280 °C). In addition to its high flexibility towards operating conditions, short stabilization time (<30 min) was required for the process to reach permanent and stable regime when the operating condition setpoints were changed. Simulations were performed to investigate different process chains efficiency for producing SNG (Substitute Natural Gas) compliant with natural gas grid standards. A process chain composed of the fluidized bed reactor studied in this article followed by a condensation step, a partial recirculation stream to the reactor inlet, and a polishing reactor was proved to be an interesting solution to produce high quality SNG with reduced equipment and compression cost. The present reactor together with the specific metal-based catalyst developed in this study appear as a very efficient and flexible solution for PtM application.